Unbiased Decisions Among Women’s Basketball Referees - Gomez-Gonzalez, Carlos; Dietl, Helmut; Nesseler, Cornel (Frontiers in Psychology, 2020)
Decisions often reflect implicit biases. Ethnic, racial, and gender traits are associated with stereotypes that may influence the decision-making process. Previous research shows that referees’ decisions in men’s professional sports are often biased in favor of racial and nationalistic in-groups. This study examined if similar biases exist in women’s professional sports. Additionally, this study analyzed the potential influence of the gender composition of referee teams on rapid decisions. We gathered data on referee foul calls in women’s professional basketball in Spain, 2014–19, and defined important decisions (fifth fouls) and stressful situations (one-possession matches). The main finding is that out-groups based on racial (i.e., Blacks) and nationalistic (i.e., foreign players) criteria did not differ in number of foul calls received. In stressful situations, foreign players actually received fewer fouls than Spanish players. Similarly, there was no evidence of bias due to the gender composition of referee teams: foul calls did not differ between all-male and mixed teams. Implications for race and nationality as dynamic social constructs within ethnocentric and social identity theories are discussed.